Debaryomyces hansenii CBS 8339 β-glucan enhances immune responses and down-stream gene signaling pathways in goat peripheral blood leukocytes. (November 2018) - Angulo, Miriam; Reyes-Becerril, Martha; Tovar-Ramírez, Dariel; Ascencio, Felipe; Angulo, Carlos
Abstract: Debaryomyces hansenii -derived β-glucan has shown immunostimulant effect on aquaculture species and recently on goat peripheral blood leukocytes. Moreover, the marine yeast D. hansenii CBS 8339 has demonstrated to enhance fish immune response. Nonetheless, the associated immune signaling pathways induced by β-glucan from this marine yeast have not been characterized yet. This study described the effects of β-glucan from D. hansenii CBS 8339 against challenge with Escherichia coli and activation of possible mechanisms on goat peripheral blood leukocytes. The proton nuclear magnetic resonance spectra showed that D. hansenii had β-(1, 3)(1, 6)-glucan. The phagocytic ability enhanced after E. coli challenge, and nitric oxide production increased before and after challenge in leukocytes stimulated with D. hansenii β-glucan. In addition, an early gene expression stimulation was found related to β-glucan recognition by TLR2 and Dectin-1 receptors, intracellular regulation by Syk, TRAF6, MyD88 and transcription factor NFκB, and effector functions of pro-inflammatory cytokine, such as IL-1β and TNF-α. Interestingly, simulation with D. hansenii -derived β-glucan increased leukocyte viability after E. coli challenge. In conclusion, β-glucan from D. hansenii CBS 8339 reduced cytotoxic effects of E. coli and modulated signaling pathways and innate immune response in goat peripheral blood leukocytes. Highlights: Structural characterization of D. hansenii CBS 8339 glucan revealed (1–3)-β-D-glucan. D. hansenii β-glucan reduced cytotoxic effects caused by E. coli in goat leukocytes. β-glucan enhanced phagocytic ability after E. coli challenge. β-glucan immunostimulation increased NO production before and after challenge. D. hansenii β-glucan modulated receptor, regulator and effector gene expressions in goat leukocytes.